Responses of Soil Microbial Biomass and Enzyme Activities to Tillage and Fertilization Systems in Soybean (Glycine max L.) Production - Heidari, Gholamreza; Mohammadi, Khosro; Sohrabi, Yousef (Frontiers in Plant Science, 2016)
Tillage operation and fertilizer type play important roles in soil properties as far as soil microbial condition is concerned. Information regarding the simultaneous evaluation of the effect of long-term tillage and fertilization on the soil microbial traits of soybean farms is not available. Accordingly, it was hypothesized that, the microbial biomass and enzyme activity, more often than not, respond quickly to changes in soil tillage and fertilization. Therefore, the experiments were aimed at analyzing the responses of soil microbial traits to tillage and fertilization in a soybean field in Kurdistan University, Iran. The field soil is categorized into coarse Loamy, mixed, superactive, calcareous, and mesic Typic Xerorthents. The experiments were arranged in split plot, based on randomized complete block design with three replications. Main plots consisted of long-term (since 2002) tillage systems including conventional tillage (CT), minimum tillage (MT) and no-tillage (NT). Eight fertilization methods were employed in the sub-plots, including (F1): farmyard manure (FYM); (F2): compost; (F3): chemical fertilizers; (F4): FYM + compost; (F5): FYM + chemical fertilizers; (F6): compost + chemical fertilizers; (F7): FYM + compost + chemical fertilizers and (F8): Control (without fertilizer). The highest microbial biomass carbon (385.1 μg) was observed in NT-F4 treatment. The NT treatment comparatively recorded higher values of acid phosphatase (189.1 μg PNP g-1 h-1), alkaline phosphatase (2879.6 μg PNP g-1 h-1) and dehydrogenase activity (68.1 μg PNP g-1 h-1). The soil treated with a mixture of compost and FYM inputs had the maximum urease activity of all tillage treatments. Organically manured treatment (F4) showed more activity in dehydrogenase (85.7 μg PNP g-1 h-1), acid phosphatase (199.1 µg PNP g-1 h-1) and alkaline phosphatase (3183.6 µg PNP g-1 h-1) compared to those treated with chemical fertilizers. In NT-F4 treatment, using on-farm inputs is most suitable for sustainable management and improvement in soil biological activities in soybean cultivation. We concluded that applying organic manures and employing reduced tillage systems increased soil microbial biomass and enzyme activities.